The thread of life : the story of genes and genetic engineering - Aldridge, Susan (New York : Cambridge University Press, 1998)
Examines genetic engineering, explores the field of molecular biology, discusses DNA and its importance to genetic engineering, and looks at the field of biotechnology and how genetic engineering can be applied to such problems as producing vegetarian cheese or cleaning up the environment.
Includes bibliographical references (p. [253]-254) and index.
Adult
Keywords: Biotechnology; DNA; Genetic engineering; Genetics; Biotechnology; DNA; Genetic engineering; Genetics